Observations of player (de)selection within a professional UK soccer academy - Kite, R. J.; Noon, M. R.; Morris, R.; Clarke, N. D. (Journal of Science in Sport and Exercise, 2024)
The present study engaged in an ethnographical observation of the processes used to determine player (de)selections within a professional academy. English category-2 youth academy players (n = 96) from U10-U16 age groups undertook anthropometric profiling (height, mass and somatic maturation) and fitness assessments (10 m, 20 m & 30 m linear sprints, 505-agility test, countermovement and squat jumps). Each players lead coach (n = 4) subjectively graded players utilising a red, amber and green (RAG) rating system on a weekly (current performance) and quarterly (perceived potential) basis, across 25 weeks. A MANCOVA, controlling for maturation, was applied to determine differences in (de)selection by physical performance. Mann Whitney-U tests were used to distinguish difference in (de)selection by subjective grading (weekly and quarterly). The key finding was that quarterly subjective gradings established a higher cumulative score of green ratings in selected players and a low cumulative score of red ratings, and vice versa for deselected players (P = 0.001 to 0.03). However, whilst these findings suggest that quarterly subjective grades of potential were able to provide the best predictors for player (de)selection, the findings should be viewed with caution due to high potential for confirmatory bias.